Eludryl Pro as Part of a Treatment Package for the Prevention of Reimplantation (Eurasian Medical Research Periodical, 2022)
One of the urgent tasks of dentistry is the prevention and correction of dental defects. Modern methods of prosthetics are used, one of which is the implant method. In spite of the modern technology in this method, there are complications, the most frequent of which are maxillary sinusitis (45,3%), neuritis (35,5%), peri-implantitis (19,2%).